2018
DOI: 10.3390/ijerph15102209
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiological Influence of Climatic Factors on Shigellosis Incidence Rates in Korea

Abstract: Research has shown the effects of climatic factors on shigellosis; however, no previous study has evaluated climatic effects in regions with a winter seasonality of shigellosis incidence. We examined the effects of temperature and precipitation on shigellosis incidence in Korea from 2002–2010. The incidence of shigellosis was calculated based on data from the Korean Center for Disease Control and Prevention (KCDC, Cheongju, Korea), and a generalized additive model (GAM) was used to analyze the associations bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
2
9
0
1
Order By: Relevance
“…[25] In Korea, the incidence of shigellosis increased by 13.6% with a temperature increase of 1°C. [37] Similar to previous studies, [25,29,37] the present study found that temperature was positively associated with the risk of shigellosis, with a rise of 1°C in air temperature corresponding to an 8% increase in the risk of disease.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…[25] In Korea, the incidence of shigellosis increased by 13.6% with a temperature increase of 1°C. [37] Similar to previous studies, [25,29,37] the present study found that temperature was positively associated with the risk of shigellosis, with a rise of 1°C in air temperature corresponding to an 8% increase in the risk of disease.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is similar to the findings in the USA, Denmark, Australia, China, and Bangladesh, which all found that rainfall did not directly affect shigellosis. [8,3739] However, some studies from the Pacific Islands reported a dose-response relationship between rainfall and the incidence of shigellosis, [16] suggesting that extremely high and low values of rainfall may lead to an increase in the number of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, although the incidence of shigellosis has a decreasing trend in China [16,21,22], it is still relatively high level in Hubei province from 2005 to 2017. The difference incidence of shigellosis cases in male and female is observed by the descriptive epidemiology [23,24]. However, all of them do not clarify the reasons for the difference.…”
Section: Epidemiological Characteristicsmentioning
confidence: 98%
“…In recent years, although the incidence of shigellosis exhibited a decreasing trend in China [6,26,36], relatively high levels still occurred in Hubei Province from 2005 to 2017. Different incidences of shigellosis cases in males and females were observed by the descriptive epidemiology [37,38]. However, few clarifications of the causes of this difference and the transmission features have been provided.…”
Section: Epidemiological Characteristicsmentioning
confidence: 99%